IKLAN LAYANAN MASYARAKAT PENTINGNYA PENGGUNAAN MASKER PADA MASA PANDEMI COVID 19 BERBASIS WEB MOBILE - Setya Nugraha, Andre Eka; RACHMAN, ANUNG (Institut Seni Indonesia Surakarta, 2021)
In this study, the discussion focuses on public service advertisements. The purpose of using this advertisement is to determine the effect of the advertisement on public awareness to use masks during the pandemic. During the COVID-19 pandemic, there are many ways to protect yourself. One of them is the Community Movement Using Masks (Gemas). This study uses qualitative research methods using a literature and empirical approach. Then the data is obtained from several regulations, such as the regulation of the governor of DKI Jakarta and phenomena that occur in the field. This advertisement is used as a means to socialize the use of masks during the pandemic and to assist the government in breaking the chain of distribution of the COVID-19 virus. The results showed that advertising had an influence on people's behavior. The results of this data are in accordance with the concepts of mass communication theory and advertising, both of which have the aim of influencing and changing people's behavior to use masks. This study uses qualitative methods, qualitative methods are methods that collect data in the form of words or sentences.Keyword: advertising, mobile web, masks, pandemic